Spreader Graft in Closed Rhinoplasty: The “Rail Spreader” - Scattolin, Alberto; Orlando, Niana; D'Ascanio, Luca (Facial Plastic Surgery, 2013)
Spreader grafts (SGs) have been widely used for both aesthetic and functional reasons to prevent middle vault collapse and treat internal nasal valve insufficiency. Although SG precise fixation can be easily achieved in open rhinoplasty, the difficulties of SG placement in closed rhinoplasties can be discouraging. In the present report, we describe a new custom-made SG (called “rail spreader”) and the personal easy method of application of such graft in “endonasal” rhinoplasty. The technical details and results are reported along with the advantages of our technique over previously described approaches.
Keywords: spreader graft; closed rhinoplasty; rail spreader; surgical technique